Analysis of the Wage Payment System from the Perspective of Imam Maliki Case Study of the Crackers Industry in Panyabungan - Defriza, Rita (PT Agung Media Publisher, 2025)
This study analyzes the wage payment system in the cracker industry in Panyabungan from the perspective of Imam Maliki's thoughts. Wage payment practices in this industry often do not align with the principles of justice and agreements prescribed in Islam, necessitating an in-depth examination. This study employs a qualitative approach with a case study method. Data were collected through observations, in-depth interviews with workers and business owners, and literature studies on Imam Maliki's views regarding wage systems. The findings indicate that the wage payment system in the cracker industry in Panyabungan tends to be non-transparent and is often implemented on a daily basis without written contracts. From Imam Maliki’s perspective, this system has shortcomings as it does not fully ensure workers' rights. Discussions with business owners revealed that economic factors and production efficiency are the primary reasons for maintaining this practice. This study reveals that although the wage system in the cracker industry has been practiced for generations, it still does not fully comply with the principles of justice in Islam according to Imam Maliki. This research has limitations in terms of geographical coverage and the number of participants. Therefore, future research can expand the study area and compare wage payment systems with the perspectives of other Islamic schools of thought.